Sistem Informasi Bank Data Alumni Peserta Diklat Di BPSDM Provsu Berbasis Web - Hulu, Tri Suasana; Manurung, Immanuel H G (Universitas Sari Mutiara Indonesia, 2023)
Alumni Data Bank Information System for Training Participants at BPSDM Provincial Based Currently, the web is still done manually, namely by saving alumni data in the ledger, filling in alumni data is deemed less efficient and effective. Admin manages training participant alumni data on the computer Using Microsoft Excel one by one, it takes quite a bit of time long. The author's goal is to create an alumni-based data management system website using the PHP and MySQL programming languages ​​for database management. The input data is name, NIP, registration number, rank & class, religion, agency, home address, office address, results and class year. Meanwhile, the output is alumni data information. Result of This research can simplify and speed up the admin's work in viewing and managing alumni data.